The Characteristics of Tortilla Chips Made from Proportions of White Corn Flour and Tapioca, and NaHCO3 Addition - Balqis Rosalinda; Rosida, Rosida; Putra, Andre Yusuf Trisna (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Tortilla chips are snacks with thin and crispy characteristics made from the main ingredient of corn flour. This study used white corn flour, tapioca flour, and NaHCO3. In this study, white corn flour was used as the main ingredient for making tortilla chips, tapioca flour was used as a binder, and sodium bicarbonate was used to add texture. The purpose of this study was to determine the effect of the proportion of white corn flour: tapioca flour, and the addition of NaHCO3 on the characteristics of tortilla chips and to obtain the best treatment based on good physical, chemical, and organoleptic properties, and preferred by panelists. The design of this study was a Completely Randomized Design (CRD) with two factors, namely the proportion of white corn flour: tapioca flour (90:10, 80:20, 70:30) and the addition of sodium bicarbonate (0.2%, 0.4%, 0.6%). The best treatment was tortilla chips with a proportion of white corn flour: tapioca flour (70:10) with the addition of sodium bicarbonate (0.2%). The treatment resulted in a moisture content of 8.89%, ash content of 6.00%, protein content of 11.02%, lipid content of 4.64%, starch content of 60.40%, amylose content of 12.25%, amylopectin content of 48.15%; and the average organoleptic results showed a color preference score of 3.76 (like); aroma 3.84 (like); taste 4.16 (like); and texture 3.88 (like), total dietary fiber content of 4.71%, and calcium content of 493.85 mg/100g. Contribution to Sustainable Development Goals (SDGs):Goal 2: Zero HungerGoal 3: Good Health and Well-beingGoal 8: Decent Work and Economic GrowthGoal 12: Responsible Consumption and ProductionGoal 17: Partnerships for the Goals